Metamodelling Architecture for Modelling Domains with Different Mathematical Structure - Mezhuyev, Vitaliy (2014)
The new metamodelling approach for domain specific modelling is proposed in the paper. The additional level of the metamodelling architecture is introduced, which gives the possibility of metamodels development in the different mathematical semantics. This allows to take into account the mathematical structure of modelled domains, and to use the mathematical operations for development of new effective methods for solving domain specific tasks. The applicability of the approach for development of metamodels for modelling different domains is shown.